Integration of SOR Models in Explaining Traveller Behavior: A Systematic Literature Review of Empirical Studies from 2019–2025 (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This systematic literature review explores the application of the Stimulus-Organism-Response (SOR) model in understanding tourist behavior, focusing on empirical studies from 2019 to 2025. The tourism industry, a key economic driver globally, necessitates a deep understanding of tourist behavior to develop effective marketing strategies and enhance the tourist experience. The SOR model, which examines the impact of external stimuli on tourists' psychological and emotional responses, offers a comprehensive framework for analyzing tourist behavior. This review synthesizes findings from recent studies to highlight how external stimuli such as destination image, social media marketing, and sensory experiences affect tourists' perceptions, motivations, and behaviors, influencing their loyalty and intention to revisit destinations. It also discusses the role of internal factors, including satisfaction, trust, and tourist engagement, in mediating the response to external stimuli. The findings suggest that understanding these dynamics can help destination managers and tourism marketers design more targeted and sustainable marketing strategies. The review also identifies gaps in the current literature and provides recommendations for future research, particularly in the integration of digital technologies and the increasing importance of sustainability in tourism behavior.